Auditory guidance of eye movements toward threat-related images in the absence of visual awareness - Hu, Junchao; Badde, Stephanie; Vetter, Petra (Frontiers in Human Neuroscience, 2024)
The human brain is sensitive to threat-related information even when we are not aware of this information. For example, fearful faces attract gaze in the absence of visual awareness. Moreover, information in different sensory modalities interacts in the absence of awareness, for example, the detection of suppressed visual stimuli is facilitated by simultaneously presented congruent sounds or tactile stimuli. Here, we combined these two lines of research and investigated whether threat-related sounds could facilitate visual processing of threat-related images suppressed from awareness such that they attract eye gaze. We suppressed threat-related images of cars and neutral images of human hands from visual awareness using continuous flash suppression and tracked observers’ eye movements while presenting congruent or incongruent sounds (finger snapping and car engine sounds). Indeed, threat-related car sounds guided the eyes toward suppressed car images, participants looked longer at the hidden car images than at any other part of the display. In contrast, neither congruent nor incongruent sounds had a significant effect on eye responses to suppressed finger images. Overall, our results suggest that only in a danger-related context semantically congruent sounds modulate eye movements to images suppressed from awareness, highlighting the prioritisation of eye responses to threat-related stimuli in the absence of visual awareness.